Risk factors for hospital outcomes in pulmonary embolism: A retrospective cohort study - Lüthi-Corridori, Giorgia; Giezendanner, Stéphanie; Kueng, Cedrine; Boesing, Maria; Leuppi-Taegtmeyer, Anne B.; Mbata, Munachimso Kizito; Schuetz, Philipp; Leuppi, Joerg D. (Frontiers in Medicine, 2023)
Background: Pulmonary embolism (PE) is not only a life-threatening disease but also a public health issue with significant economic burden. The aim of the study was to identify factors - including the role of primary care – that predict length of hospital stay (LOHS), mortality and re-hospitalization within 6 months of patients admitted for PE. Method: A retrospective cohort study was conducted with patients presenting to a Swiss public hospital with PE diagnosed at the hospital between November 2018 and October 2020. Multivariable logistic and zero- truncated negative binomial regression analyses were performed to assess risk factors for mortality, re-hospitalization and LOHS. Primary care variables encompassed whether patients were sent by their general practitioner (GP) to the emergency department and whether a GP follow-up assessment after discharge was recommended. Further analyzed variables were Pulmonary Embolism Severity Index (PESI) score, laboratory values, comorbidities, and medical history. Results: A total of 248 patients were analyzed (median 73 years and 51.6% females). On average patients were hospitalized for 5 days (IQR 3-8). Altogether, 5.6% of these patients died in hospital, and 1.6% died within 30 days (all-cause mortality), 21.8% were re-hospitalized within 6 months. In addition to high PESI scores, we detected that, patients with an elevated serum troponin, as well as with diabetes had a significantly longer hospital stay. Significant risk factors for mortality were elevated NT-proBNP and PESI scores. Further, high PESI score and LOHS were associated with re-hospitalization within 6 months. PE patients who were sent to the emergency department by their GPs did not show improved outcomes. Follow-up with GPs did not have a significant effect on re- hospitalization. Conclusion: Defining the factors that are associated with LOHS in patients with PE has clinical implications and may help clinicians to allocate adequate resources in the management of these patients. Serum troponin and diabetes in addition to PESI score might be of prognostic use for LOHS. In this single-center cohort study, PESI score was not only a valid predictive tool for mortality but also for long-term outcomes such as re-hospitalization within 6 months.